2014
DOI: 10.1144/sp402.5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal fluids in epithermal and porphyry Au deposits in the Central Slovakia Volcanic Field

Abstract: The Neogene Central Slovakia Volcanic Field in the Carpathian arc contains various Au deposits, hosted by central zones of large andesite stratovolcanoes. Fluids involved in mineralization have bee n studied at three different types of deposit, mostly by fluid inclusion and stable isotope techniques. Rozália mine in the Štiavnica stratovolcano hosts intermediate sulphidation style Au-Ag epithermal mineralization in subhorizontal veins, related to hydrothermal activity during an early stage of caldera collapse.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…(Konečný et al 1983). The results of K-Ar isotope dating of Kraus et al 1994;Koděra et al 2014). Bentonite deposits: Stará Kremnička -Jelšový potok (1); Stará Kremnička III (2); Lutila I (3); Lutila -Pod Klapou (4); Bartošova Lehôtka (5); Kopernica (6) and Dolná Ves (7).…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…(Konečný et al 1983). The results of K-Ar isotope dating of Kraus et al 1994;Koděra et al 2014). Bentonite deposits: Stará Kremnička -Jelšový potok (1); Stará Kremnička III (2); Lutila I (3); Lutila -Pod Klapou (4); Bartošova Lehôtka (5); Kopernica (6) and Dolná Ves (7).…”
Section: Geological Settingmentioning
confidence: 99%
“…The thickness of bentonite beds ranges from a few metres up to 50 m (Šamajová et al 1992). The bentonite beds are often interbedded with limnic/lacustrine silicites which are formed by SiO 2 discharge from the subsurface hydrothermal fluids upon reaching the local limnic/lacustrine basins (Koděra et al 2014). The previous studies have reported that bentonite deposits of the Jastrabá Fm.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…One is dedicated to currently exploited deposits of the Central Slovakia Volcanic field and another to a sedimentary-hosted epithermal prospect from the Tertiary Eastern Rhodopes (Bulgaria). The Rozália, Kremnica, and Biely Vrch mines studied by Koděra et al (2014) are three epithermal-porphyry deposits of economic importance currently exploited in the Central Slovakia Volcanic field of the Carpathian arc, one of the most important AuAg mining regions of Europe since the 14th -15th century. The peculiarity of these Neogene deposits is that they form different styles of Au deposits within two coalescent stratovolcanoes (Š tiavnica and Javorie).…”
Section: Historical and Disciplinary Contextmentioning
confidence: 99%
“…At Kremnica and Rozália, the mineralization is hosted by coupled sets of transtension/extension faults filled with quartz, carbonates and sulphides (pyrite, galena, sphalerite, chalcopyrite, proustite, pyrargyrite), while at Biely Vrch the deposit is made of a Au-bearing stockwork of quartz, sulphides and Fe-Ti oxide crosscutting an hydrothermally altered rock rich in kaolinite, pyrophyllite, chlorite and K-feldspar. Koděra et al (2014) constrain the properties of the Au-transporting ore fluids of these deposits using a dataset made of fluid inclusion microthermometry, oxygen and carbon isotope analyses, and quantification of clay mineral abundance of altered rocks by XRD analyses. These data are used in conjunction with age relationships and well-constrained field relationships to propose a genetic model of the three deposits.…”
Section: Historical and Disciplinary Contextmentioning
confidence: 99%